THE IMPACT OF GREEN BANKING IMPLEMENTATION ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS A MEDIATOR (A Study on Islamic Commercial Banks Registered with the Financial Services Authority for the Period 2022-2024) - Nunik Nurmalasari; Erika Dahlia; Tigin Lugiani; Jojo Jojo (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
This study examines the effect of green banking on firm value in Islamic Commercial Banks in Indonesia during the 2022–2024 period, with financial performance as a mediating variable. Guided by legitimacy, stakeholder, and signaling theories, the study employs a quantitative approach using panel data regression. Green Banking is measured by the Green Banking Disclosure Index (GBDI), Firm Value by Tobin’s Q, Financial Performance by Return on Assets (ROA), and Company Size by the natural logarithm of total assets as a control variable. The findings indicate that green banking has a negative effect on financial performance but a positive effect on firm value. Financial performance does not significantly influence firm value and is not proven to mediate the relationship. These results suggest that green banking enhances firm value primarily through improved reputation and social legitimacy rather than financial performance.